The relationship between the atherogenic index of plasma and postoperative myocardial injury following non-cardiac surgery under general anaesthesia: a retrospective cohort study - Yuanjun Zhou; Liping Zhong; Yilin Liao; Yuting Zhong (BMC Cardiovascular Disorders)
Abstract Background The atherogenic index of plasma (AIP) is a reliable lipid marker associated with coronary artery stenosis (CAS) and cardiovascular events. However, the relationship between AIP and myocardial injury after non-cardiac surgery (MINS) remains insufficiently explored. Methods This retrospective study included adult patients who underwent non-cardiac surgery under general anaesthesia. The primary exposure was preoperative AIP, with MINS as the primary outcome. The predictive accuracy of AIP for MINS was assessed using the area under the curve (AUC). Restricted cubic splines (RCS) were used to explore the potential nonlinear relationship between AIP and MINS. Logistic regression analysis was conducted to examine the association of AIP with MINS. Subgroup and interaction analyses were carried out across multiple factors, including age, gender, body mass index, medical history, and the type of surgery (emergency or elective). Results The cohort consisted of 1,160 adult patients, with a median preoperative AIP of -0.05. The incidence of MINS was 7.9%. The AUC for AIP in predicting MINS was 0.719, surpassing the AUCs of triglycerides and high-density lipoprotein cholesterol (0.644 and 0.683, respectively). RCS analysis demonstrated a linear relationship between AIP and MINS (P for nonlinear = 0.165). Patients in the highest quartile of AIP had significantly higher odds of developing MINS than those in the lowest quartile (adjusted OR, 8.05; 95% confidence interval [CI], 3.44 to 18.80; P < 0.001). The results across most subgroups were consistent with the primary analysis, showing no significant interaction effects. Conclusions A significant and independent linear relationship exists between preoperative AIP and the risk of MINS. As an economical and easily accessible lipid marker, AIP holds potential for preoperative screening of patients at risk of postoperative cardiovascular events.